Hambatan Hambatan Guru PJOK dalam Implementasi 7 Kebiasaan Anak Indonesia Hebat - Tamami, Muhammad Khairul; Mashud; Recky Ahmad Haffyandi (UNIB Press, 2025)
This study aims to explore the obstacles experienced by physical education teachers in implementing exercise habits as part of the 7 Great Indonesian Children's Habits program at the elementary school level of Banjarbaru City. The research approach used is a mixed method with a sequential explanatory design, namely the collection of quantitative data first through a Likert scale questionnaire to 18 physical education teachers, then followed by in-depth interviews with 16 teachers who experienced the most dominant obstacles. The results of the quantitative analysis show that most of the 9 physical education teachers face obstacles in the medium category with a percentage 50%, with the main obstacles being a lack of facilities and facilities, low student participation, and lack of support from families. Meanwhile, qualitative data confirm that although teacher motivation is quite high, the implementation of monitoring sports activities and the use of supporting technology is still limited. The conclusions of this study emphasize the importance of collaboration between teachers, schools, parents, and the government in supporting the program. Efforts to increase teacher capacity through training, provision of adequate sports facilities, and the integration of sports habits into the curriculum and overall school culture are the main recommendations. The results of this research are expected to be used as a basis for consideration in designing strategic policies to strengthen character education through sustainable physical activities in the elementary school environment.